Modeling UPS and enhancing the capability by integrating renewable sources - Mojumder, Arijit; Rahat, Md. Raisul Haque; Khan, MD. Abdur Rahim; Ahamed, Ajaz (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.